An alternative for proteinase K-heat-sensitive protease from fungus Onygena corvina for biotechnology: cloning, engineering, expression, characterization and special application for protein sequencing - Piotr M. Skowron; Daria Krefft; Robert Brodzik; Paulina Kasperkiewicz; Marcin Drag; Klaus-Peter Koller (Microbial Cell Factories, 2020)
Abstract Background A neutral, heat-sensitive serine protease (NHSSP) originating from the feather-degrading fungus Onygena corvina (O. corvina) was described and defined as an alkaline serine protease of the subtilisin type S8 family, exhibiting an enzymatic activity at neutral pH. Generally, broad specificity proteases, such as proteinase K or trypsin, have found numerous applications in research and biotechnology. Results We report the cloning and expression in the yeast PichiaPink™ system, as well as purification, and characterization of the NHSSP. Recombinant, His6-tagged NHSSP was efficiently expressed from an optimized, synthetic gene and purified using a simple protocol based on ammonium sulfate fractionation and hydrophobic interaction chromatography. The enzyme shows atypical C-terminal processing, the coded preproprotein undergoes signal peptide removal and maturation through the clipping of a propeptide section and 10 amino acids (aa) from the C-terminus, including the His6-tag. The deletion variant has been constructed, devoid of the C-terminal ORF segment, thus eliminating the need for C-terminal processing. Both NHSSP variants exhibit very similar enzymatic characteristics. The purified enzymes were characterized to determine the optimal proteolytic conditions. We revealed that the mature NHSSP is reproducibly active over a wide pH range from neutral to mild acidic (pH of 5.0 to 8.5), with an optimum at pH 6.8, and at temperatures of 15 to 50 °C with an optimum at 38–42 °C. Interestingly, we demonstrated that the protease can be fully deactivated by a moderate increase in temperature of about 15 °C from the optimum to over 50 °C. The protease was partially sensitive to serine protease inhibitors, and not inhibited by chelating or reducing agents and detergents. SDS induced autolysis of NHSSP, which points to a high stimulation of its proteolytic activity. Conclusions The NHSSP was produced as a recombinant protein with high efficiency. Compared to proteinase K, the most common serine protease used, NHSSP shows an approx. twofold higher specific activity. Protein sequencing can be a valuable technical application for the protease. The protein coverage is significantly higher in comparison to trypsin and reaches about 84–100% for β-lactoglobulin (BLG), antibody (mAb) light and heavy chains. Furthermore, the option to perform digestions at neutral to slightly acidic pH-values down to pH 5.0 avoids modification of peptides, e.g. due to deamidation.